2017
DOI: 10.1002/lary.26739
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human papillomavirus awareness in association with head and neck cancer at a screening event

Abstract: NA. Laryngoscope, 128:386-392, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…The study reported that women were 2.5 times more likely than men and younger individuals were also more likely to be aware of the HPV link. 19 Younger age groups are more likely to be aware of HPV risk as they are targeted for HPV vaccination. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that women were 2.5 times more likely than men and younger individuals were also more likely to be aware of the HPV link. 19 Younger age groups are more likely to be aware of HPV risk as they are targeted for HPV vaccination. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…With the rise in Human Papilloma Virus (HPV) related cancers of the head and neck, public awareness of this viral risk factor has increased but is still only at 12 -28% [2][3][4] . Oral sex, increased number of sexual partners, and early age at first sexual encounter are associated with an increased risk of HNC 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The general population knowledge of head and neck cancer and its risk factors is poor 2 . The general population is most familiar with smoking as a risk factor for head and neck cancer (HNC), with 54 -65% correctly identifying smoking as a risk factor [2][3][4] . With the rise in Human Papilloma Virus (HPV) related cancers of the head and neck, public awareness of this viral risk factor has increased but is still only at 12 -28% 2-4 .…”
Section: Introductionmentioning
confidence: 99%
“…Opportunistic screening for HNC is recommended by professional societies during routine healthcare visits[2,3]. Oral cancer maintains a relatively low public awareness[4-6], despite its prevalence as the 6 th most common cancer in the US. For the last decade, our multidisciplinary team has held a HNC screening day to help raise awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were counseled on tobacco cessation, but alcohol cessation guidance was not performed systematically. Given the relatively low public awareness that alcohol is an additive risk factor for HNC[4,6] this provides an opportunity to improve our practices by offering counseling regarding alcohol consumption[9]. We also did not ask patients about sexual habits that have been linked to human papillomavirus (HPV) exposure[10].…”
Section: Discussionmentioning
confidence: 99%